Oral hygiene effects verbal and nonverbal displays of confidence. Issue 2 (4th March 2021) - Taylor, Paul; Banks, Faye; Jolley, Daniel; Ellis, David; Watson, Steven; Weiher, Lynn; Davidson, Brittany; Julku, Juliaana
ABSTRACT: Although oral hygiene is known to impact self-confidence and self-esteem, little is known about how it influences our interpersonal behavior. Using a wearable, multi-sensor device, we examined differences in consumers' individual and interpersonal confidence after they had or had not brushed their teeth. Students (N = 140) completed nine one-to-one, 3-minute "speed dating" interactions while wearing a device that records verbal, nonverbal, and mimicry behavior. Half of the participants brushed their teeth using Close-Up toothpaste (Unilever) prior to the interactions, whilst the other half abstained from brushing that morning. Compared to those who had not brushed their teeth, participants who had brushed were more verbally confident (i.e., spoke louder, over-talked more), showed less nonverbal nervousness (i.e., fidgeted less), and were more often perceived as being "someone similar to me." These effects were moderated by attractiveness but not by self-esteem or self-monitoring.